Indebted to development: microcredit as (de)marginalisation in rural China. Issue 3 (19th March 2018) - Loubere, Nicholas
Abstract : Microcredit schemes have been increasingly incorporated into development policies that aim to de-marginalise rural China. Based on in-depth ethnographic fieldwork, this paper examines the various roles that microcredit programmes play in development outcomes at the local level. It demonstrates that microcredit has the ability to facilitate the de-marginalisation of certain individuals/groups, while simultaneously (re)producing inequalities, thus exacerbating the marginalisation of others. This finding demonstrates that microcredit does not induce uniform, predictable and linear development through the integration of marginal places and people into the formal financial system and wider economy. Instead, microcredit programmes reflect and reinforce the interlocking sets of unequal relationships that are the root cause of marginality and underdevelopment in China. Through this detailed analysis of the contradictory outcomes of Chinese microcredit programmes, this paper provides the basis for a wider relational critique of microcredit as an intervention aimed at inducing a specific type of market-oriented linear development that is beneficial for some and detrimental for others.